2019
DOI: 10.1111/mpp.12808
|View full text |Cite
|
Sign up to set email alerts
|

NbALD1 mediates resistance to turnip mosaic virus by regulating the accumulation of salicylic acid and the ethylene pathway in Nicotiana benthamiana

Abstract: Summary AGD2‐LIKE DEFENCE RESPONSE PROTEIN 1 (ALD1) triggers plant defence against bacterial and fungal pathogens by regulating the salicylic acid (SA) pathway and an unknown SA‐independent pathway. We now show that Nicotiana benthamiana ALD1 is involved in defence against a virus and that the ethylene pathway also participates in ALD1 ‐mediated resistance. NbALD1 was up‐regulated in plants infected with turnip mosaic virus (TuMV).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…However, the abovementioned elicitor's effective concentration is between μg/mL and mg/mL in order of magnitude, which is considerably higher than the working concentration of ZNC (ng/mL), such as Flg22 (1 μM, approximately 2.232 μg/ mL) and OGs (50 μg/mL) [48]. Moreover, several plant hormones' working concentration is higher than that of ZNC; for example, the antiviral concentration of SA is 10 μM, approximately 1.38 μg/mL [26]. ZNC is the fermentation extract from p. variotii, mainly containing nucleoside, saccharides, protein and other compounds (data not shown).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the abovementioned elicitor's effective concentration is between μg/mL and mg/mL in order of magnitude, which is considerably higher than the working concentration of ZNC (ng/mL), such as Flg22 (1 μM, approximately 2.232 μg/ mL) and OGs (50 μg/mL) [48]. Moreover, several plant hormones' working concentration is higher than that of ZNC; for example, the antiviral concentration of SA is 10 μM, approximately 1.38 μg/mL [26]. ZNC is the fermentation extract from p. variotii, mainly containing nucleoside, saccharides, protein and other compounds (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…Salicylic acid (SA) is a key plant hormone that mediates host responses against microbial pathogens. This plant hormone induces important plant defense response against pathogens [22][23][24][25][26]. Previous studies have shown a possible overlap between RNA-silencing pathway and signal transduction pathways governed by SA [27][28][29][30]; for example, the NtRDRP activity has been increased in tobacco plants after SA treatment [29].…”
Section: Backgroudmentioning
confidence: 99%
“…P1Pro upregulated several genes associated with SA signaling, including NPR3 homologs and a wide array of PR genes from different families ( Supplemental Figure 2 ). Pipecolic acid is a metabolite that can act synergistically with SA to promote plant immunity ( Hartmann and Zeier, 2019 ; Wang et al, 2019 ); homologs of its core signaling components ALD1 , WRKY33 , and SARD1 were also upregulated in P1Pro samples. RNA-silencing components, including AGO1 and AGO2 , were downregulated in P1Pro samples ( Supplemental Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, a genome-wide analysis showed that P1Pro, a PPV clone that lacks the P1 autoinhibitory domain, triggered complex transcriptomic changes that included the SA and possibly the pipecolate pathways, central components of plant systemic acquired resistance and antiviral immunity ( Hartmann and Zeier, 2019 ; Wang et al, 2019 ; Murphy et al, 2020 ). Infection of SA signaling-defective hosts led to the identification of additional players in P1Pro-induced responses, and meta-analysis using our transcriptomic datasets and those of hormone-treated A. thaliana plants highlighted the contribution of ABA.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments with exogenous ethylene provide a safe and effective method for control of pear browning [43]. Exogenous application of ACC, the precursor of ET, enhanced the resistance of NbALD1-transgenic plants of Nicotiana benthamiana to Turnip mosaic virus [44].…”
Section: Discussionmentioning
confidence: 99%